Il curricolo multiculturale e le competenze di comunicazio- ne interculturale degli insegnanti: riflessioni a partire dal caso brasiliano - Laura Cristina Vieira Pizzi; Glenda Galeotti (Firenze University Press, 2014)
This article proposes a reflection on multicultural curriculum in Brazil and its implications in the relationship between education, identity and citizenship. From these considerations, the reflection continuies on the training of teachers working in multicultural contexts, with a specific focus on their intercultural communicative skills. The analysis relies, in particular, on the contributions of cultural and postcolonial pedagogical framework in which, from its origin in the Anglo-Saxon context, engage in unmask hegemonic tendencies of certain policies, models and educational practices, which for years have been prevailing in the contexts of formal education.